Artificial insemination: a potential technique for doubling goat farmers’ income - Ranjan, R; Singh, M K; Dixit, A K (Indian Farming, 2018)
Artificial Insemination has not attained the large-scale adoption inour country. Attempts were made to find out the reason behind this and improved the quality and quantity of semen.There is an increasing awareness of the benefits that frozen semen technology offers to the controlled animal breeding and husbandry.